2005
DOI: 10.1017/s0022377804003459
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory experiment to investigate auroral kilometric radiation emission mechanisms

Abstract: If an initially mainly rectilinear electron beam is subject to significant magnetic compression, the conservation of the magnetic moment results in the ultimate formation of a horseshoe distribution in phase space. A similar situation occurs where particles are accelerated into the auroral region of the Earth's magnetic dipole. Such a distribution has been shown to be unstable to a cyclotron resonance maser type of instability and it has been postulated that this may be the mechanism required to explain the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
31
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 9 publications
3
31
0
Order By: Relevance
“…5). Figure 6 shows the results of numerical simulations with the PIC code KARAT, 24 where the horseshoe formation evident as the beam moves into the stronger magnetic field, and its subsequent saturation after the emissions occur can be seen. For near perpendicular propagation the resonant electrons, determined by the cyclotron resonance condition (1), have almost constant energy and if the parameters are such that they lie along the inside of the horseshoe the system is unstable to cyclotron instability.…”
Section: Satellite Observations and The Horseshoe Shaped Momentumentioning
confidence: 99%
“…5). Figure 6 shows the results of numerical simulations with the PIC code KARAT, 24 where the horseshoe formation evident as the beam moves into the stronger magnetic field, and its subsequent saturation after the emissions occur can be seen. For near perpendicular propagation the resonant electrons, determined by the cyclotron resonance condition (1), have almost constant energy and if the parameters are such that they lie along the inside of the horseshoe the system is unstable to cyclotron instability.…”
Section: Satellite Observations and The Horseshoe Shaped Momentumentioning
confidence: 99%
“…In all cases, the cyclotron-maser instability is presumed to be driven by an electron horseshoe or modified horseshoe-ring distribution. Scaled laboratory experiments have demonstrated the potential for such horseshoe distributions to generate narrowband cyclotron-maser emission at GHz frequencies over distances of a few meters [21][22][23][24][25].Although the generation mechanism is well established, there remain important questions with regard to how the radiation may propagate within the parent auroral density cavity and ultimately escape [26]. Cairns et al [27] have demonstrated how the radiation, generated just below the electron cyclotron frequency, may successfully couple onto the upper branch of the plasma dispersion relation and escape.…”
mentioning
confidence: 99%
“…In all cases, the cyclotron-maser instability is presumed to be driven by an electron horseshoe or modified horseshoe-ring distribution. Scaled laboratory experiments have demonstrated the potential for such horseshoe distributions to generate narrowband cyclotron-maser emission at GHz frequencies over distances of a few meters [21][22][23][24][25].…”
mentioning
confidence: 99%
“…The main research themes include gyro-devices with particular emphasis on gyro-TWAs [1,2] and gyro-BWOs, and natural sources of radiation such as auroral kilometric radiation (AKR) [3][4][5][6], novel Cherenkov mm-wave sources [7,8] and pseudospark-driven sub-THz sources [9][10][11].…”
mentioning
confidence: 99%